Uji Kepekaan Sel Biofilm Isolat Klinik Staphylococcus aureus Penyebab OMSK di RSUP dr. Sardjito Terhadap Antibiotik Vancomycin Secara In Vitro - , CLARADYKA NACHITA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: Chronic Suppurative Otitis Media (CSOM) is a chronic middle ear infection that usually happened in childhood and can cause hearing problems. Staphylococcus aureus as one of the causative agents is highly potential in developing biofilm that further complicates CSOM treatment. Currently there is a reduced susceptibility of S. aureus to vancomycin, which is commonly used to treat planktonic staphylococcal infection, while a higher dose is needed to treat biofilm. Objectives: To evaluate the susceptibility of S. aureus biofilm to vancomycin in vitro, particularly Minimum Biofilm Reduction Concentration 50 (MBRC50). Methods: This study used a descriptive observational method. Samples were obtained from middle ear secretion of patients with CSOM in ENT polyclinic, Dr. Sardjito Hospital during October-December 2012. S. aureus was grown in vitro as biofilm and exposed to different concentrations of vancomycin. MTT assay was used to determine MBRC50. Results: In the concentration of 32 Î¼g/ml, 50% reduction of S. aureus biofilm growth was observed. Conclusion: Vancomycin was able to achieve MBRC50 for S. aureus biofilm in the concentration of 32 Î¼g/ml.